Study effect of extreme wind direction change on 3-bladed horizontal axis wind turbine - Le Quang Sang; Takao Maeda; Yasunari Kamada (International Journal of Renewable Energy Development, 2019)
The Horizontal Axis Wind Turbines (HAWT) are used very popular in the world. They were installed mainly on land. However, on the land, the wind regime change is very complex such as high turbulence and constantly changing wind direction. In the International Electrotechnical Commission (IEC) 61400-1 standard, the wind regime is devided into the normal wind conditions and the extreme wind conditions. This study will focus on the extreme wind direction change and estimate the aerodynamic forces acting on a 3-bladed HAWT under this condition. Because the extreme wind direction change may cause extreme loads and it will affect the lifetime of HAWTs. This issue is experimented in the wind tunnel in Mie University, Japan to understand these effects. The wind turbine model is the 3-bladed HAWT type and using Avistar airfoil for making blades. A 6-component balance is used to measure the forces and the moments acting on the entire wind turbine in the three directions of x, y and z-axes. This study estimates the load fluctuation of the 3-bladed wind turbine under extreme wind direction change. The results show that the yaw moment and the pitch moment under the extreme wind direction change fluctuate larger than the normal wind condition. Specifically, before the sudden wind direction change happened, the averaged maximum pitch moment MX is -1.78 Nm, and after that MX is 4.45 Nm at inrush azimuth of 0°.©2019. CBIORE-IJRED. All rights reserved